STRATEGI PENERAPAN BUDAYA 3S (SENYUM, SALAM, SAPA) DALAM MENUMBUHKAN KARAKTER PESERTA DIDIK DI SDN LEMAHPUTRO 1 SIDOARJO - Ita Amellia, Solehah; Muhammad Yusron Maulana El-Yunusi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The strategy for implementing the 3S (Smile, Greet, Greet) culture is a simple but very effective program for developing students' personalities and building a harmonious school atmosphere and can instill polite and polite attitudes that respect each other and build positive relationships. The purpose of this research is to understand the impact of 3S cultural education on individual social change. This researcher collected data by conducting interviews which were obtained from the experience of the subject students and teachers in their routine habits of implementing the 3S culture which will be used as a data collection technique in this ongoing research in the field by the researcher.